Challenges Facing Financial Inclusion Due to the COVID-19 Pandemic (European Journal of Marketing and Economics, 2020)
Financial inclusion is often considered as an access to financial resources for the wide public and small and medium-sized businesses, although it is a much broader concept and includes a wide range of access to quality financial products and services, including loans, deposit services, insurance, pensions and payment systems. Mechanisms for protecting the rights of consumers of financial products and services are also considered to be subject to financial inclusion. Financial inclusion acquires great importance during the pandemic and post-pandemic period. The economic crisis caused by the pandemic is particularly painful for low-income vulnerable population. A large part of the poor population who were working informally has lost source of income due to lockdown from the pandemic. Remittances have also been reduced / minimized, as the remitters had also lost jobs and are unable to send money home. Today, when people die from Coronavirus disease, it may be awkward to talk about the financial side of a pandemic, but the financial consequences can be far-reaching if steps are not taken today to ensure access to and inclusion of financial resources. The paper examines the impact of the pandemic on financial inclusion and the responses of the governments and the financial sectors to the challenge of ensuring the financial inclusion of the poor population and small and medium enterprises.
Keywords: financial inclusion, economic growth, access to financial products and services, pandemic, low-income population